Albuminúria and factors associated with chronic kidney disease in obesity (Research, Society and Development, 2021)
Introduction: Albuminuria is an important marker for increased morbidity and mortality in obese and a screening parameter for early renal changes. However, few studies associate the impact of obesity on albuminuria. Objective: To relate albuminuria and risk factors for chronic kidney disease with obesity. Methods: Cross-sectional study with obese patients, over 18 years old, without a diagnosis of chronic kidney disease, allocated according to the Body Mass Index, in groups A (30-39,99 kg/m² and 40-49 kg/m²) and B (≥50 kg/m² and ≥60 kg/m²). Renal evaluation occurs through the measurement of albuminuria, urea and creatinine. Lipid, inflammatory and glycemic profile were also evaluated. Chi-square, student t, Mann-Whitney and Spearman correlation tests were performed, with the Statistical Package for the Social Sciences software. The results were achieved with a significance level of p